2015
DOI: 10.1177/0004563215578191
|View full text |Cite
|
Sign up to set email alerts
|

Faecal calprotectin as a marker for oesophago-gastric cancer

Abstract: Faecal calprotectin is elevated in patients with cancer of the upper gastrointestinal tract. This study suggests that calprotectin may be promising in discriminating cancer patients from controls, but further work is required to explore any potential role of faecal calprotectin in screening for, or diagnosis of, oesophago-gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“… Negretti et al (2020) used a porcine-ligated loop model to study the porcine intestinal response to Campylobacter jejuni infection and found that the abundance of inflammatory cytokines IL -8 and TNF -α were substantially increased during infection. Vincent et al (2015) used calmodulin in stool as a marker of inflammatory diseases. S100A9 amplifies inflammatory responses’ and plays a key point in the involvement of organisms in immune-related responses ( Vincent et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Negretti et al (2020) used a porcine-ligated loop model to study the porcine intestinal response to Campylobacter jejuni infection and found that the abundance of inflammatory cytokines IL -8 and TNF -α were substantially increased during infection. Vincent et al (2015) used calmodulin in stool as a marker of inflammatory diseases. S100A9 amplifies inflammatory responses’ and plays a key point in the involvement of organisms in immune-related responses ( Vincent et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“… Vincent et al (2015) used calmodulin in stool as a marker of inflammatory diseases. S100A9 amplifies inflammatory responses’ and plays a key point in the involvement of organisms in immune-related responses ( Vincent et al, 2015 ). The ROS levels in the intestine can cause various problems ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a meta‐analysis concluded that the overall sensitivity and specificity of fecal calprotectin in the diagnosis of colorectal cancer were 36 and 71%, and that it was not recommended as a screening test for colorectal malignancies in the general population . Among 39 patients with known esophageal gastric cancer and 191 control subjects, fecal calprotectin had a sensitivity of 76.9% and a specificity of 88.0% in the diagnosis of esophageal gastric cancer, using the manufacturer’s cut‐off value <50 mg/g . Our previous studies have shown that fecal BAFF was elevated in IBD patients, but its role in gastrointestinal cancer is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…diseases and malignancies have been discussed [26][27][28][29][30][31][32]. To the best of our knowledge, no similar study has been performed on fecal calprotectin level in patients with MM, so this study was designed to revealed the possible association.…”
Section: Plos Onementioning
confidence: 99%